2019
DOI: 10.4236/jep.2019.109068
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Noise Pollution in Northern Industrial Areas of Windhoek, Namibia

Abstract: The increase in industrial activities and vehicular movement along the northern industrial area of Windhoek has vastly increased the amount of traffic noise and other noise pollution in the area. Noise pollution has an adverse health effect to human population, when exposed for a long period. Residence in proximate communities along the north industrial area and those working in the various industries located in the area may be affected, when the noise pollution level exceed the permissible standard for human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, it is important to raise awareness about the adverse effects of excessive exposure to noise pollution and potential hearing loss. Raising awareness is in line with the WHO regulations as environmental noise is currently deemed a public health issue globally, but more particularly in developing countries where a study conducted by Onjefu 37 indicated that traffic noise is the major source of noise pollution. In developing countries, researchers have lamented the fact that noise is not properly recognised 38 nor are policies on noise regulations strictly enforced in places deemed noisy or surpassing permissible noise levels.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, it is important to raise awareness about the adverse effects of excessive exposure to noise pollution and potential hearing loss. Raising awareness is in line with the WHO regulations as environmental noise is currently deemed a public health issue globally, but more particularly in developing countries where a study conducted by Onjefu 37 indicated that traffic noise is the major source of noise pollution. In developing countries, researchers have lamented the fact that noise is not properly recognised 38 nor are policies on noise regulations strictly enforced in places deemed noisy or surpassing permissible noise levels.…”
Section: Discussionmentioning
confidence: 81%
“…Noise monitoring is used to assess critical sound pressure levels in residential, commercial, and industrial areas under different environmental conditions. In addition, noise monitoring can serve to validate and/or verify noise modeling predictions, and to establish and/or strengthen national and local sound pressure level monitoring programmes [46][47][48][49][50][51].…”
Section: Challenges In Developing Countries In the Field Of Environme...mentioning
confidence: 99%
“…In Nairobi, the capital city of Kenya, Public Service Vehicles (PSVs) generated noise limit of about 95.9 dBA with the minimum noise level in the northern part recording 92.2 dBA, western part having 88.7 dBA, southern part having 83.1 dBA and eastern part having 81.2 dBA respectively thereby causing serious Noise-Induced Hearing Loss (NIHL), physiological as well as psychological restlessness [9] . In the city of Windhoek, Namibia, vehicular and industrial activities contributed noise pollution ranging between 64 dBA ~ 72 dBA thereby exceeding the WHO standard of 70 dBA in residential areas [10,11] .…”
Section: Introductionmentioning
confidence: 99%